Use of statistics as a decision making tool in a technical feasibility study of the post stirring method in a steel plant (Research, Society and Development, 2020)
The purpose of this study is to demonstrate the importance of using quality tools in a large steel company. In this work, the use of statistical tools to support the decision on the use of the Post Stirring method is demonstrated. This method allows the steel quality  improvement  with less cost. Results of process application were compared with results before its application. The boxplot, histogram, hypothesis test and linear regression tools were used. Results obtained from analysis of information collected by statistical methods were the basis for decision making. Results showed that the Post Stirring technique brings a reduction in phosphorus content and in the amount of oxygen dissolved in steel, providing a great opportunity to reduce costs by reducing consumption of deoxidizing materials. In addition, it promotes a significant improvement in the steel's clarity, bringing benefits to the final product.